Death and Chronic Disease Risk Associated With Poor Life Satisfaction: A Population-Based Cohort Study. Issue 2 (27th October 2018) - Rosella, Laura C; Fu, Longdi; Buajitti, Emmalin; Goel, Vivek
Abstract: Life satisfaction is increasingly recognized as an important determinant of health; however, prospective population-based studies on this topic are limited. We estimated the risk of chronic disease and death according to life satisfaction among a population-based cohort in Ontario, Canada ( n = 73, 904). The cohort included 3 pooled cycles of the Canadian Community Health Survey (2003–2008) linked to 6 years of follow-up (to 2015), using population-based health databases and validated disease-specific registries. The databases capture incident and prevalent cases of diabetes, cancer, chronic obstructive pulmonary disease, heart disease, and death. Multivariable Cox proportional hazard models were used to estimate hazards of incident chronic disease and death, and were adjusted for sociodemographic, behavioral, and clinical confounders, including age, sex, comorbidity, mood disorder, smoking, alcohol consumption, physical activity, body mass index, immigrant status, education, and income. In the fully adjusted models, risk of both death and incident chronic disease was highest for those most dissatisfied with life (for mortality, hazard ratio = 1.59, 95% confidence interval: 1.15, 2.19; for chronic disease, hazard ratio = 1.70, 95% confidence interval: 1.16, 2.51). In this population-based cohort, poor life satisfaction was an independent risk factor for incident chronic disease and death, supporting the idea that interventions and programs that improve life satisfaction will affect population health.